1988
DOI: 10.1152/ajprenal.1988.254.2.f210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atrial natriuretic factor on renal function in rats with nephrotic syndrome

Abstract: This study was designed to evaluate the renal effects of atrial natriuretic factor [ANF(8-33)] in rats with aminonucleoside (AMN)-induced nephrotic syndrome. AMN (100 mg/kg iv) was administered to adult female rats either 2 (AMN 2, n = 7), 4 (AMN 4, n = 7), 6 (AMN 6, n = 7), or 14 (AMN 14, n = 6) days before clearance experiments; untreated (UNT, n = 7) animals served as controls. During clearance experiments, rats were anesthetized with pentobarbital sodium. Protein excretion rates were similar between UNT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…These observations support those of Hildebrant & Banks (1988) in rats with nephrotic syndrome, induced with aminonucleoside, and those of Sterzel et al (1987), using rats with antiglomerular basement membrane nephritis, who found atrial natriuretic peptides were still able to increase the excretion of water and sodium. In this latter report there were concomitant increases in glomerular filtration rate.…”
Section: Discussionsupporting
confidence: 89%
“…These observations support those of Hildebrant & Banks (1988) in rats with nephrotic syndrome, induced with aminonucleoside, and those of Sterzel et al (1987), using rats with antiglomerular basement membrane nephritis, who found atrial natriuretic peptides were still able to increase the excretion of water and sodium. In this latter report there were concomitant increases in glomerular filtration rate.…”
Section: Discussionsupporting
confidence: 89%
“…The blunt natriuretic/diuretic response to ANP in rats with experimentally induced NS is a well-established finding that we [14] and other investigators [6,7,9,10,11,12,13,14,15,16,17,18] have previously documented. The inability of the kidney to normally increase sodium excretion in response to ANP, which is also observed in other edema-forming states such as congestive heart failure [19,20,21,22] and liver cirrhosis [23], has been postulated as an important mechanism leading to salt retention and edema formation [9,11,13,24].…”
Section: Discussionsupporting
confidence: 57%
“…The natriuretic/diuretic response to either saline load [4,5,6,7] or exogenous infusion of atrial natriuretic peptide (ANP), an important regulator of water and Na + balance [8], is markedly attenuated in rats with ADR-induced NS [8,9,10,11,12,13,14,15]. It has been suggested that the diminished renal responsiveness to ANP may contribute to the pathogenesis of salt retention and edema formation in NS [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our experiments suggest that the defect in sodium metabolism in at least one form of experimental nephrosis, that resulting from adriamycin administration, may result from blunted cellular responsiveness to the renal actions of ANP. Other studies have documented that rats treated with adriamycin have a blunted natriuretic response to volume expansion (7) and ANP infusion (19)(20)(21). In recent studies, renal denervation improved both the volume expansion natriuresis (7) and the natriuresis resulting from infusion of ANP IMCD cells .7…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies carried out in rats with nephrosis resulting from adriamycin administration have suggested that the ab-normal sodium metabolism accompanying this disorder could reflect impaired responsiveness to circulating ANP (19)(20)(21). This resistance to the natriuretic action of ANP and the blunted natriuresis seen after volume expansion in these rats were shown to improve after renal denervation (7,19).…”
Section: Introductionmentioning
confidence: 99%